Peningkatan Kemampuan Pembukuan Pada Ukm Bakmi Pak Gembong - Febrina Nafasati Prihantini; Dian Indudewi; Alfa Vivianita (STIE Malangkucecwara, 2021)
One of the characteristics of small industries is that they still face many obstacles, both in terms of production and business management. The production aspect includes technology/equipment, production continuity, quality uniformity, packing, labeling, etc., while in the business management aspect there is not much support for promotions, marketing development strategies, and limited distribution and bookkeeping of business results. The same thing happened to Bakmi Pak Gembong who was in Rejosari Village, East Semarang District. Where Pak Gembong's Bakmi Business is still a small-scale industry that also has problems in terms of management, especially in terms of recording the results of its business. To overcome these problems, Community Service activities were carried out by providing counseling about the importance of recording all matters relating to the operation of a business. The expected outcome of this Community Service activity is that SME actors have an understanding of the importance of recording their business on a regular basis and the benefits derived from recording business operations on a regular basis.